STRUCTURAL INDICATORS OF EDUCATIONAL ACTIVITY IN UNIVERSITIES OF PHYSICAL CULTURE - Petrov, S.I. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to reveal the direction of the structural indicators of educational activity in higher educational institutions of physical culture. Methods and structure of the study. As part of the implementation of the first stage of the state task on the topic "Integration of educational, scientific and physical culture and sports activities in higher education in the field of physical culture and sports", the educational activities of higher education institutions of physical culture were monitored according to the main structural indicators and special scientific and methodological literature was studied on this issues. Results and conclusions. The data on the sports qualification of the contingent and the teaching staff in educational institutions are presented. The ratio of various structural divisions and indicators of methodological support of training in educational institutions are determined. The analysis carried out will serve as the basis for the development of evidence-based proposals for the normative, organizational and methodological support of the process of integrating the educational, scientific and sports activities of full-time bachelor students in higher education institutions of physical culture.